O financiamento da Extensão: contribuições para o estudo dos casos da Universidade Federal de São Carlos/Brasil e da Universidade de Lisboa/Portugal - Incrocci, Lígia Maria de Mendonça Chaves (Universidade Federal de São Carlos, 2019)
This work has the goal to understand the universitary extension/third mission strengthening in the scientific field from the public notices ProxExt/MEC in Brazil and Horizonte 2020 in Portugal. The research locus are the Sao Carlos Federal University/Brazil and Lisbon University/Portugal. The data collection went through the researcher presence in the European country as a result of a research fomentation scholarship of the Programa de Doutorado Sanduiche no Exterior (PDSE), during the period between the months of September and December of 2017. Starting point for the proposed analysis, the ProExt/MEC and Horizonte 2020 public notices are considered the main notices in regards to the extension/third mission, in the respective countries. The analysis of those will help us comprehend the strengthening of research projects that incorporate in their practice the local knowledge, the social development bias and the valorization of the community beyond the university walls. For this purpose, we question: In which manner should we talk about approximation, democratization and mediation without having all the actors effectively involved and heard? Who are the scientists doing the extension/third mission in the university scope? For what and for who do they do it? What are the power struggles implied in the extension/third mission production? How is the extension/third mission contabilized for the scientific capital gathering? These and other questions, as well as the analysis of the gathered data, have allowed us to conclude that the inclusion of the society in the position of a further element present in the structure of the scientific field didn`t have the effect envisaged in the analyzed notices. In other words, the rules of the aforementioned field weren`t altered in function of the extension/third mission strengthening, and the structure remains unchanged in the hierarchic way university/community.
The University Extension funding: contributions to the case studies of the Federal University of São Carlos / Brazil and the University of Lisbon / Portugal
Keywords: Extensão universitária; Terceira via; Campo científico; Universidade de Lisboa; Universidade Federal de São Carlos; University extension; Third mission; Scientific field; Lisbon University; São Carlos Federal University; CIENCIAS HUMANAS